Escuchando ladrar a los perros: Hernando de Soto y su receta para la Amazonía - Wieland, Patrick (2013)
The work of Peruvian economist Hernando de Soto is both influential and controversial. His 2000 bestseller The Mystery of Capital posits that to solve poverty in the developing world, the poor need to transition from the extralegal sector to the official economy through formal property rights and incorporated businesses. In 2009, following the 2009 bloody clashes of indigenous peoples and law enforcement agents in the Peruvian Amazon, DeSoto suggested the extrapolation of The Mystery of Capital to the Amazon as a solution for their underdevelopment. He contended that the Amazon natives could only progress if granted formal title to land and allowed to create limited liability corporations. This paper argues, however, that the purported extrapolation of The Mystery of Capital’s propositions is problematic. It aims to show that economic integration of the Amazon natives may further expose their land resources to appropriation and, in actuality, trigger their cultural, social and environmental disintegration.